HISTORICAL COSTS VS. DEFERRED COSTS AS BASIC CONCEPTS FOR FINANCIAL STATEMENT VALUATIONS. - Shugerman, Abe L. (The Accounting Review, 1951)
This article focuses on the financial statements valuation. Where two alternative procedures each have compensating advantages and disadvantages, it is possible to design a procedure that will combine them so as to amalgamate their advantages and eliminate their undesirable features. Fortunately, such a process is possible in the conflict between historical costs and deferred costs concepts. Since each theory has its obvious merits, there is much to be said for preparing two separate sets of statements, with one set being predicated on historical costs and the other being based on the deferred cost concept. Or, single statements could be prepared with two distinct sets of values. Such a procedure would have the salutary effect of fuller reporting of accounting data, and a greater usefulness of such information. It would, of course, mean an increase in the cost of accounting services, but accounting has become such an important adjunct of commerce that additional costs for vital information should easily be justified. The need for a dual value statement is not an entirely new one, since the traditional "Statement of Affairs" really expresses this same basic thought. However, the development of other dual value statements has undoubtedly been inhibited because they represent a sharp departure from strict precedent, rather than because these statements are either inherently unsound or fundamentally undesirable. It is believed that a new approach is certainly needed, and that there is compelling evidence to justify it.